2021
DOI: 10.1037/adb0000674
|View full text |Cite
|
Sign up to set email alerts
|

Gambler clusters and problem gambling severity: A cluster analysis of Swedish gamblers accessing an online problem gambling screener.

Abstract: It has been proposed that overall gambling involvement has a stronger association with problem gambling (PG) than any specific game type. However, few studies have used multiple analytic approaches on the same data set to assess these relationships. The aims of the current study were to identify patterns of gambling activity (PGAs) and to assess the relationships between different game types, PGAs, gambling involvement, and PG as measured by the Problem Gambling Severity Index (PGSI), using two different appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
3
7
0
Order By: Relevance
“…Importantly, gambling on high-risk games was the strongest predictor of gambling problems and increased gambling frequency both during the first and second wave of the pandemic. These findings support previous research which shows that certain game types, such as online casino games and EGMs, are associated with PG ( Binde et al, 2017 ; Wall et al, 2020 ). Further, a recent study from the United Kingdom found that the vast majority stopped or reduced their gambling involvement during lockdown, but among men who switched game types, PG was more common ( Sharman et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Importantly, gambling on high-risk games was the strongest predictor of gambling problems and increased gambling frequency both during the first and second wave of the pandemic. These findings support previous research which shows that certain game types, such as online casino games and EGMs, are associated with PG ( Binde et al, 2017 ; Wall et al, 2020 ). Further, a recent study from the United Kingdom found that the vast majority stopped or reduced their gambling involvement during lockdown, but among men who switched game types, PG was more common ( Sharman et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…A Swedish study found that past-month gambling during the pandemic had a stronger association with PG compared to past year gambling for several game types (i.e., any sports betting, land-based casinos, and EGMs); however, for online horse betting, an opposite association was found ( Håkansson, 2020 ). This is in line with previous research pointing toward an important indicator of PG which is frequent gambling on high-risk games, such as EGMs and online casinos, a relationship that is well established ( Binde et al, 2017 ; Wall et al, 2020 ). These high-risk games are characterized by short intervals between bet and outcome and when a new bet can be placed, which provides almost unlimited gambling opportunities ( Griffiths and Auer, 2013 ).…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…The helpline is funded by the government and has no affiliations with the gambling industry. Previous research on the helpline’s online problem gambling screener indicate that gamblers who come in contact with the helpline via its webpage experience severe gambling problems (Wall, Berman, Jayaram-Lindström, Hellner, & Rosendahl 2020 ). The helpline also offers an online self-help program without therapist support at its website for gamblers who want to change their gambling habits on their own.…”
Section: Methodsmentioning
confidence: 99%